A Silent Threat: Deep Vein Thrombosis in Early-Stage Parkinson’s Disease - Li Y; Fan H; Wei W; Zhu H; Wang H; Lyu D; Zhang Z; Tan Y (Dove Medical Press, 2024)
Yang Li,1,* Huihui Fan,2,* Wei Wei,3 Hanyu Zhu,4 Haifeng Wang,4 Dayao Lyu,1 Zengrui Zhang,1 Ying Tan1 1Department of Neurology, Huzhou Central Hospital, The Fifth School of Clinical Medicine of Zhejiang Chinese Medical University, Huzhou, People's Republic of China; 2Department of Ultrasound, Huzhou Central Hospital, The Fifth School of Clinical Medicine of Zhejiang Chinese Medical University, Huzhou, People's Republic of China; 3Department of Key Laboratory of Basic Research and Clinical Translation, Huzhou Central Hospital, The Fifth School of Clinical Medicine of Zhejiang Chinese Medical University, Huzhou, People's Republic of China; 4Department of Neurology, Medical School of Huzhou University, Huzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Ying Tan, Email zzftyzhy@126.comIntroduction: The primary clinical manifestation of venous thrombosis is discomfort in the lower extremities. Some early Parkinson's disease (PD) patients feel discomfort in the lower limbs. Venous thrombosis can risk lives by causing pulmonary embolism. This study examines the incidence of DVT in early PD patients and its correlation with different clinical and lab features.Methods: A cross-sectional study was conducted on 117 patients with early-stage PD. Ultrasonography was employed to detect the presence of DVT. Factors such as age, gender, body mass index, lifestyle habits (smoking and drinking), medical history (hypertension, diabetes, atrial fibrillation, and tumor), and other lab tests linked to thrombosis were analyzed.Results: In 117 patients, 11 (9.4%) had DVT, while 106 (90.6%) did not. There were no significant differences in gender, BMI, habits, medical history, or other thrombosis-related tests between both groups. However, DVT patients were older with higher d-dimer levels. They also showed an increased right substantia nigra ultrasound echo area, higher HY grades, higher UPDRS 3 scores, less improvement in UPDRS 3 scores and levodopa response.Discussion: The primary risk factors for lower extremity venous thrombosis were found to be age, d-dimer levels, and low-dose levodopa. Therefore, for elderly patients with early-stage PD, it is crucial to conduct d-dimer and lower extremity vascular ultrasound tests. The prevention of venous thrombosis in the lower extremities of early PD patients is of utmost importance.Keywords: deep vein thrombosis, early-stage, Parkinson's disease, ultrasonography, risk